Financial Ratio Analysis Of State-Owned Enterprises (SOE) In The City Of Palembang - Siregar, Muhammad Ichsan; Cahyadi, Afriyadi; Igamo, Alghifari Mahdi; Saggaf, Abdullah; Sulbahri, Rifani Akbar (Catholic University Musi Charitas, 2022)
This study aims to determine the solvency and profitability of State-Owned Enterprises (SOE) in the city of palembang. This study uses a quantitative descriptive approach. The population of this research is State-Owned Enterprises (SOE) and the sampling method was PT. Pupuk Sriwidjadja (Persero) and PT. Semen Baturaja (Persero) was period 2014-2018. The solvency ability of PT Pupuk Sriwidjadja (Persero), seen from the Debt to Asset Ratio and Debt to Equity Ratio, was in a bad condition from 2014-2018. Meanwhile, the ability of profitability to return on assets and return on equity has decreased period 2014-2018. The solvency ability of PT Semen Baturaja (Persero) seen from the Debt to Asset Ratio period 2014-2017 is in good condition. Meanwhile, in 2018 it was quite good and the Debt to Equity Ratio was in good condition in 2014-2018. Meanwhile, the ability of profitability to return on assets and return on equity has decreased period 2014-2018. The limitations of this study are of the many existing financial ratios, researchers only use the solvency and profitability ratios that represent each variable, the research period was only conducted for 4 years from 2014 to 2018, the sample used in this study is a state-owned company in the city of Palembang. The contribution of this research is related to the analysis of debt and income used by the Palembang city state-owned enterprises. Keywords: Solvency, Profitability, State-Owned Enterprises (SOE)